2020
DOI: 10.1063/1.5116554
|View full text |Cite
|
Sign up to set email alerts
|

Vibration energy harvesting with piezoelectric ceramics working in d33 mode by using a spring-mass-spring oscillator

Abstract: This paper proposed a piezoelectric energy harvester based on a spring-mass-spring oscillator, of which the piezoelectrics operate in the d33 mode. Theoretical analysis reveals that the spring-mass-spring oscillator can not only generate a larger vibration than that of the ambient system but also buffer the force of possible accidental impact applied on the piezoelectric stacks. By using lead zirconate titanate (PZT-4) ceramics as model materials, we systematically characterized the performance of the energy h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The open-circuit voltage could be improved through reducing the size of damping orifice, where the output voltage reached the maximum value of 51.6 V at the air pressure of 0.5 MPa with the valve opening of 1/6. Li et al (2020) proposed a piezoelectric energy harvester based on a spring-mass-spring oscillator, of which the piezoelectrics operate in the d33 mode. By using lead zirconate titanate (PZT-4) ceramics as model materials, they systematically characterized the performance of the energy harvester.…”
Section: Resultsmentioning
confidence: 99%
“…The open-circuit voltage could be improved through reducing the size of damping orifice, where the output voltage reached the maximum value of 51.6 V at the air pressure of 0.5 MPa with the valve opening of 1/6. Li et al (2020) proposed a piezoelectric energy harvester based on a spring-mass-spring oscillator, of which the piezoelectrics operate in the d33 mode. By using lead zirconate titanate (PZT-4) ceramics as model materials, they systematically characterized the performance of the energy harvester.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the structural vibration characteristics under friction, including the transformation between dynamic and static frictions [17], system stability analysis [18,19], and energy harvesting under friction [20,21] have received attention from researchers. Studies have been conducted on vibration response [22][23][24] and energy harvesting from friction [25][26][27][28][29][30]. Li et al solved the final wear shape of elastic indenter by the dimension reduction method.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al proposed a piezoelectric energy harvester based on spring mass oscillator. The results showed that the harvester can output high voltage at resonant frequency [ 28 ]. Chen et al sandwiched the piezoelectric plate between two layers of elastic damping elements and proposed a method to realize energy harvesting through frictional vibration and vibration reduction at the same time [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vibration energy harvesters (VEHs), which can harvest energy from ambient vibrations and convert it into electrical energy automatically, have become a promising alternative for a range of applications. There are three main approaches to harvesting energy from vibrations, which involve the use of either electrostatic [1][2][3][4][5][6], electromagnetic [7,8] or piezoelectric [9][10][11][12][13][14][15][16][17][18][19] principles. As a general rule, the main challenge in vibrational energy harvesting is that the maximum system performance is achieved when the resonant frequency of the VEH matches the external vibration source.…”
Section: Introductionmentioning
confidence: 99%